Effect of Accounting Conservatism in Managing the Risk of Downside of Operating Cash Flows of Companies Listed in Amman Stock Exchange: An Analytical Study - Hamad, Amneh; AL-Momani, Mohammad (Jordan Journal of Business Administration, 2018)
This study aimed to investigate the effect of conditional and unconditional accounting conservatism on managing the risk of downside of operating cash flow in the companies listed in Amman Stock Exchange (ASE) for the period (2005 – 2014). To achieve the research objectives, the study was applied on a sample of (166) companies and focused on the use of a compound measure generated from the three measures of conditional conservatism; accumulation of non-operating accruals, proportion of accounting conservatism to good news and proportion of current accrual to total accrual. Also, the study used a compound measure generated from the three measures of unconditional conservatism; total accrual, book to market ratio and skewness. The root lower partial moment of operating cash flow was used as a measure of downside risk of operating cash flow. In order to analyze the data and test the study hypotheses, this study used descriptive statistics, correlation coefficients, factor analysis and multivariate regression. It found the following results: The companies listed in (ASE) (industrial, financial and service companies) practiced conditional and unconditional accounting conservatism, where the financial sector practiced accounting conservatism more than industry and service sectors. There is a statistically significant effect of both types of accounting conservatism on the downside risk of operating cash flow in the financial reports of the companies listed in (ASE). One of the main recommendations of the study urges companies that suffer from downside risk of operating cash flow to practice an appropriate degree of accounting conservatism.